Penerapan Nilai Kejujuran dalam Praktik pada Perspektif Ekonomi Islam - Hani Fuadatun Nafisa; Indri Purwanti; Silvianingsih Silvianingsih; Zaskia Adya Mecca; Lina Marlina (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2026)
Business activities are essential for helping the economy of society function properly. When starting a business, people usually want to make money, but they are also supposed to follow good values, like being honest in their dealings. In real life, some businesses still do unfair things, like giving false information about products, changing prices unfairly, lowering the quality of goods, and using incorrect measurements when selling items. This research focuses on explaining what honesty means and how it should be used in business according to the principles of Islamic economics. The study uses a qualitative method called literature review, which involves looking at books, journal articles, and other sources that talk about Islamic business ethics. The results show that honesty is a key value in Islamic business because it helps build trust with customers, ensures fair deals, and creates positive relationships between sellers and buyers. The value of honesty in the business world can be demonstrated through transparancy of information about products, honesty in pricing, accuracy in measurement, and not hiding defects in the goods being sold. From an Islamic economics perpective, business activities should not only focus on material income, but also on the value of blessings, ethical responsibility, and mutual prosperity. Thus, the application of honesty in an important foundation for building fair, transparent bisuness practices that are in line with Islamic economic prinsiples.